STRESS AMONG COLLEGE STUDENTS OF IMPHAL CITY - Jennifer Yumnam (Galaxy International Interdisciplinary Research Journal, 2022)
Stressors are defined as circumstances that disrupt, or threaten to disrupt, individuals’ daily functioning and cause people to make adjustments. Stress is perceived in different ways and may mean different thing to different individuals. Aim: This study was conducted with the aim to find the prevalence of stress among college students in Imphal City. Methods: It was a cross sectional study conducted among the college students of the government colleges located within the Imphal city area. Respondents were asked to provide certain socio-demographic variables. The Depression Anxiety Stress Scale was used to measure stress. Results: The age of the participants ranged from 17 years to 28 years with a mean of 22.5 (SD=1.6). The prevalence of stress was found to be 30.80% in this study. Conclusion: Support and mentoring are required so that stress can be identified early and dealt with appropriately. Further studies are recommended to find out the factors leading to mental disorders in students.